Electrocatalyzed water electrolysis using electrodeposited rhodium on silver alloy - Bonifacio, Ryan M. (College of Engineering, University of the Philippines Diliman, 2014)
Hydrogen has been increasingly considered as the fuel of the futue and potential alternative to fossil fuels because it is the cleanest and ideal energy carrier. Water electrolysis is one of the easiest methods for hydrogen production, offering the advantage of simplicity. This research was conducted to investigate the activity of Rh electrode for its potential electrocatalytic application as an anode and a cathode in water electrolysis. The Rh electrode was fabricated from a 5g/L solution of Rh2(SO4)3 electroplated at 3.00V for 3mins in a 92.5% Ag alloy substrate, producing a thickness of Rh deposit ranging from 1.88-2.46μm. Electrodeposited Rh was annealed at 319˚C for 1hour. Results of electrochemical characterization showed an excellent stability of Rh electrode in both acidic and alkaline water electrolysis. The electrocatalytic properties of Rh electrode were significantly affected by surface roughness, annealing and type of electrolyte. Rh electrode with higher surface roughness exhibited better overpotential (η) and exchange current density (log i_o) for HER and OER. Since annealing at 319˚C lowered the surface roughness, unannealed electrode demonstrated better electrocatalytic properties. Electrocatalytic activity of Rh electrode is better in acidic than in basic electrolyte, however on both media improve with increasing concentration of electrolyte. The limiting current on the other hand was not affected by the stirring rate which suggests that the H2 and O2 evolution on this work were not governed by mass transfer. The performance of Rh electrode on HER (η_acid~138mV, η_base~360mV; log i_o acid~-5.27 (A/cm^2), log i_o base~-5.53(A/cm^2)) and OER (η_acid~204mV, η_base~230mV; log i_o acid~-5.07(A/cm^2), log i_o base~-5.55(A/cm^2)) is comparable to that of Pt which suggests its potential as an anode and a cathode in water electrolysis. On a 48-hour continuous water electrolysis, Rh electrode showed excellent stability as an anode on both acidic and basic media. However, despite excellent electrocatalytic properties of Rh electrode for hydrogen evolution in acidic and basic media, it may fail as a cathode in long term water electrolysis. Stability as a cathode decreases with increasing electrolyte concentration at a higher rate on acidic medium.